Current Protocols for Bone Grafting in the Comprehensive Treatment of Patients with Cleft Lip and Palate - Villegas Fonseca, Javier Alonso; Núñez Hernández, Mishell Stephany; Sánchez Sánchez, Javier Estuardo (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This study aims to evaluate current bone graft protocols in the comprehensive treatment of patients with cleft lip and palate, identifying trends, challenges, and improvement strategies. A mixed methodology is employed, including a retrospective cohort study of 75 patients treated between 2021 and 2023, an 18-month prospective observational study, and a survey of 46 experts in the field. Results reveal a preference for secondary alveolar bone grafting, with an optimal intervention age between 7-9 years, with iliac crest autograft being the most utilized. High success rates were observed in graft integration and aesthetic improvements, although challenges such as graft resorption and postoperative complications persisted. Experts emphasized the importance of a multidisciplinary approach and treatment personalization, identifying a growing trend towards the use of advanced technologies such as 3D surgical planning and cell therapies. It is concluded that current protocols are evolving towards more personalized and technologically advanced treatments, with success depending on a multidisciplinary approach, appropriate intervention timing, and long-term follow-up. The persistence of challenges underscores the need for continuous research, while the integration of new techniques and materials promises to improve functional and aesthetic outcomes, highlighting the dynamic nature of the field and the importance of continuous optimization of treatment protocols